2000
DOI: 10.1021/jm0009484
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Opioid Receptor Affinity of a Series of 2,4-Diaryl-Substituted 3,7-Diazabicylononanones

Abstract: 3,7-Diazabicyclo[3.3.1]nonan-9-ones having aryl rings in positions 2 and 4 with systematically varied substituents were synthesized using a double Mannich procedure. Radioligand binding assays were performed to measure the affinity of the compounds to the mu-, delta-, and kappa-opioid receptors. The affinity of all 2, 4-diphenyl-substituted 3,7-diazabicyclo[3.3.1]nonan-9-ones to the mu- and delta-receptors was found to be low. In contrast, with exception of the nitro- and cyanophenyl-substituted compounds, mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…(Fig. 1) is a fluorphenyl derivative of HZ2, which was synthesized based on the 3,7-diazabicyclo[3.3.1]nonan-9-one skeleton (Siener et al, 2000). HZ2 exhibited high affinity for the opioid receptor in rat brain membranes (Siener et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(Fig. 1) is a fluorphenyl derivative of HZ2, which was synthesized based on the 3,7-diazabicyclo[3.3.1]nonan-9-one skeleton (Siener et al, 2000). HZ2 exhibited high affinity for the opioid receptor in rat brain membranes (Siener et al, 2000).…”
mentioning
confidence: 99%
“…1) is a fluorphenyl derivative of HZ2, which was synthesized based on the 3,7-diazabicyclo[3.3.1]nonan-9-one skeleton (Siener et al, 2000). HZ2 exhibited high affinity for the opioid receptor in rat brain membranes (Siener et al, 2000). HZ2 also showed a strong and long-lasting antinociceptive effect in the mouse tail-flick test (Kogel et al, 1998).…”
mentioning
confidence: 99%
“…However, the 2-butyl and methylcyclohexyl substituted compounds 3 and 11 exhibit an unexpected high affinity to the κ-OR. Whereas in previous studies no µ-affinities have been found for any diazabicyclononanone [3,4,5,6] HZ2 and the corresponding alkyl substituted compounds 1 -5 show affinity for the human µ-OR in the micromolar range of concentration. Since compounds of mixed affinities to the µ and κ-OR such as buprenorphine and butorphanol are of increasing interest [12], the next step of pharmacological studies will be to work out whether the compounds are agonists or antagonists at either receptors and check the analgesic activity in animals.…”
Section: 1]nonanonesmentioning
confidence: 68%
“…All compounds synthesized were subjected to radioligand binding assays using [4,5,6]. Since the affinities measured in different assays are not directly comparable, for sake of comparison HZ2, its oxalate salt, bremazocine and U-50,488 were additionally measured.…”
Section: 1]nonanonesmentioning
confidence: 99%
“…There are several reagent for removal of silyl protecting groups from hydroxyl such as ammonium fluoride 45 , tris(dimethylamino)sulfonium /difluorotrimethyl silicate 46 , hydrofluoric acid 47 and others. In this study, hydrofluoric acid was used to removal of silyl-protecting group from hydroxyl of the compound 8 to form 9 (Scheme 5 Other results showed several signals of the 1 H NMR spectrum for 22at 0.88 and 0.98 ppm for methyl bound to steroid nucleus; at 1.68 ppm for methyl group bound to imino group; at 1.40, 1.90 and 2.06-2.10 ppm for methylene groups bound to both imino and cyclobutene ring; at 1.76, 2.12 and 2.42 ppm for methylene bound to both alkyne and imino groups; at 3.10-3.56 ppm for methylene groups bound to both imino and amino groups; at 4.24 ppm for both hydroxyl and amino groups; at 6.00 ppm for cyclobutene ring; at 7.70-8.10 ppm for imino groups.…”
Section: Removal Of Silyl Fragment Of 16 or 22 Via Hydrofluoric Acid mentioning
confidence: 99%